(In) equality in the outdoors: gender perspective on recreation and tourism media in the Swedish mountains. Issue 2 (17th January 2020) - Godtman Kling, Kristin; Margaryan, Lusine; Fuchs, Matthias
ABSTRACT: This paper examines gender differences in participation in various outdoor recreation and tourism activities in the Swedish mountain region, and how these activities are portrayed from a gender perspective on the websites of five major tourist destinations. Spending time in nature has been linked to better health and well-being, and this article contributes to research on the unequal opportunities women and men have in taking part of such advantages. Results show that there is a gender difference in both participation and in representation of outdoor recreation. The observed gender difference is not only in line with the traditional heteronormativity but also suggests that new trends in outdoor recreation are further favoring traditionally masculine modes of engagement with nature. This suggests the need for re-thinking not only gender norms but also human relationships with nature in general.